The Influence Of Self-Actualization And Personality Type On Organizational Behavior And Employee Performance - Marpaung, Ivan Andeska; Tiffani, Donna Arhitania; Sopan, Mohammad Edwar; Leonando, Tito Peter (Lentera Ilmu Nusantara, 2024)
This research was conducted to determine the influence of self-actualization and personality type on organizational behavior and employee performance . In this research there are four variables, namely Self-Actualization, Personality Type, Organizational Behavior and Employee Performance . Research building on this one should look into how social media marketing and influencers affect customers' opinions of brands and their purchasing decisions. More than that, other researchers can choose to look into other research objects or expand the variety of places they conduct their studies. The research results show that Organizational behavior is positively and significantly impacted by self-actualization. The impact of personality type on organizational behavior among employees is positive and statistically significant. A person's productivity is positively and significantly impacted by their level of self-actualization. Employee performance is positively and significantly impacted by personality type. When it comes to organizational behavior, employee performance is positively and significantly impacted. Employee performance is positively and marginally impacted by self-actualization as it relates to organizational behavior. Through the medium of organizational behavior, personality type has a small but positive impact on worker productivity.